Implementasi Prinsip Pengembangan Bahan Ajar dalam Meningkatkan Prestasi Siswa di SD Islam Nailul Anwar Mukomuko - Beta Andraini; Lara Rahmayani; Nova Asvio (UIN Fatmawati Sukarno Bengkulu, 2026)
Abstract: This study aims to examine the implementation of the principles of teaching materials development, particularly the principles of relevance, consistency, and adequacy, in improving student achievement at Nailul Anwar Islamic Elementary School in Mukomuko. This study used a descriptive qualitative method with teachers and students as research subjects. Data collection techniques were carried out through observation, interviews, and documentation, while data validity was tested through triangulation of sources, techniques, and time. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the principles of relevance, consistency, and adequacy in teaching materials development can improve the quality of the learning process and student achievement as a whole in the cognitive, affective, and psychomotor aspects. The successful implementation is supported by teacher commitment, the support of the principal, a conducive learning environment, and student enthusiasm, although there are still obstacles such as limited facilities, time, and differences in student abilities. Thus, it can be concluded that the implementation of the principles of teaching materials development appropriately and systematically plays an important role in improving student achievement and the quality of the learning process. Thus, it can be suggested, to improve student achievement, increase the implementation of the principles of teaching materials development in schools.Keywords: Implementation, Principles of Teaching Material Development, Student Achievement.Abstrak: Penelitian ini bertujuan untuk mengkaji implementasi prinsip pengembangan bahan ajar, khususnya prinsip relevansi, konsistensi, dan kecukupan, dalam meningkatkan prestasi siswa di SD Islam Nailul Anwar Mukomuko. Penelitian ini menggunakan metode kualitatif deskriptif dengan subjek penelitian guru dan siswa. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi, sedangkan keabsahan data diuji melalui triangulasi sumber, teknik, dan waktu. Analisis data dilakukan melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi prinsip relevansi, konsistensi, dan kecukupan dalam pengembangan bahan ajar mampu meningkatkan kualitas proses pembelajaran dan prestasi siswa secara menyeluruh pada aspek kognitif, afektif, dan psikomotorik. Keberhasilan implementasi didukung oleh komitmen guru, dukungan kepala sekolah, lingkungan belajar yang kondusif, serta antusiasme siswa, meskipun masih terdapat kendala berupa keterbatasan fasilitas, waktu, dan perbedaan kemampuan siswa. Dengan demikian, dapat disimpulkan bahwa implementasi prinsip pengembangan bahan ajar yang tepat dan sistematis berperan penting dalam meningkatkan prestasi siswa serta kualitas proses pembelajaran. Dengan demikian dapat disarankan, untuk meningkatkan prestasi siswa, maka tingkatkanlah implementasi prinsip pengemabangan bahan ajar di sekolah. Kata Kunci: Implementasi, Prinsip Pengembangan Bahan Ajar, Prestasi Siswa.